A study of Good Agricultural Practices (GAP) toward oil palm production by smallholders at Felcra Bukit Kapah, Terengganu / Arif Afendi Mahamat - Mahamat, Arif Afendi (Faculty of Plantation and Agrotechnology, 2018)
This study was conducted to determine the factors of Good Agricultural Practices (GAP) toward oil palm production by smallholder. GAP is a manual to describe the difference technique of plantation management and ensure the standardize practices within estate and lastly will guarantee optimum productivity. While smallholders are a farmer that owning small – based plots of land on which they grow subsistence crops relying almost exclusively on family labour. There are two types of smallholder which is dependent and independent smallholder. The objective of this study is to determine the acceptance level of smallholder toward GAP and also determine the relationship between GAP to oil palm production by smallholders. This study was carried out at Felcra Bukit Kapah and the respondent is among dependent smallholder. The population in this area is 100 persons and the sample number is 80 person based on Krejrie and Morgan scale. The data of this study is gaining from the questionnaire that will distribute to the respondent. The data will be analysed by using reliability test and Statistical package for social science (SPSS). From the analysis, the researcher determines that all of the factor have strong and significant relationship and harvesting activity become the most influenced factor (p=0.000, ß=0.458, R=0.786) toward oil palm production by smallholders. GAP in harvesting activity is accepted by smallholder because this activity is important directly to the production of oil palm. For other factor, lack of knowledge and lack of fund is become the reason why smallholder do not apply GAP totally. From this study, the researcher can conclude that all of the factor of GAP toward oil palm production by smallholder have strong significant correlation relationship because all of the factor have p<0.05 and have higher Beta value. Lastly as a recommendation, the researcher that want to continue this study need to add other factor because there are other factor that can affect the oil palm production like knowledge. Next is researcher also needed to ensure that the entire respondent is valid for the studies because for example in some cases, dependent smallholders do not operate their farm himself but the operation will be conducted by foreign workers.